2006
DOI: 10.1111/j.1750-3841.2006.00001.x
|View full text |Cite
|
Sign up to set email alerts
|

Processing, Nutritional Evaluation, and Utilization of Whole Mesquite Flour (Prosopis laevigata)

Abstract: Basic crops such as wheat and maize are not cultivated easily in the central highlands of Mexico, but pods of mesquite (Prosopis laevigata), a N2−fixing plant that dominates the vegetation, could be used as an additional food source. The physicochemical and functional properties and nutritional value of whole mesquite pod flour dried at 60 °C and 70 °C and muffins prepared with the mesquite flour were investigated. Drying temperature did not change the true protein concentration of the whole mesquite pod flour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 22 publications
1
14
0
5
Order By: Relevance
“…Pods and pods fractions of Prosopis species have been described in their nutritional profile: P. africana (Igwe, Ojiako, Anugweje, Nwaogu, & Ujowundu, 2012), P. alba (Cattaneo et al, 2016;Felker, Grados, Cruz, & Prokopiuk, 2003;Sciammaro, Ferrero, & Puppo, 2016), P. chilensis (Astudillo, Schmeda-Hirschmann, Herrera, & Cortes, 2000), P. glandulosa (Harden & Zolfaghari, 1988), P juliflora (Marangoni & Alli, 1988), P. laevigata (Barba de la Rosa, Frias-Hernandez, Olalde-Portugal, & Gonzalez-Castañeda, 2006; Gallegos-Infante, Rocha-Guzman, Gonzalez-Laredo, & Garcia-Casas, 2013), P. nigra (Felker et al, 2003), P. ruscifolia (Bernardi, Sanchez, Freyre, & Osella, 2010), and P. tamarugo (Astudillo et al, 2000); active compounds content and in vitro biological activity: P. alba (Cardozo et al, 2010;Cattaneo et al, 2016;Perez et al, 2014;Sciammaro et al, 2016), P. chilensis (Astudillo et al, 2000;Briones-Labarca, Muñoz, & Maureira, 2011;Schmeda-Hirschmann et al, 2015), P. laevigata (Gallegos-Infante et al, 2013), P. nigra (Cardozo et al, 2010;Perez et al, 2014), P. ruscifolia (Bernardi et al, 2010), and P. tamarugo (Astudillo et al, 2000); and in vivo biological activity: P. glandulosa (George, Lochner, & Huisamen, 2011;Huisamen, George, Dietrich, & Genade, 2013). Nutritionally, pods of Prosopis species are gluten free (Bernardi et al, 2010;Felker et al, 2013) and rich in good quality protein (Barba de la Rosa et al, 2006) or limited in sulfur amino acids (Felker & Bandurski, 1977;Fe...…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pods and pods fractions of Prosopis species have been described in their nutritional profile: P. africana (Igwe, Ojiako, Anugweje, Nwaogu, & Ujowundu, 2012), P. alba (Cattaneo et al, 2016;Felker, Grados, Cruz, & Prokopiuk, 2003;Sciammaro, Ferrero, & Puppo, 2016), P. chilensis (Astudillo, Schmeda-Hirschmann, Herrera, & Cortes, 2000), P. glandulosa (Harden & Zolfaghari, 1988), P juliflora (Marangoni & Alli, 1988), P. laevigata (Barba de la Rosa, Frias-Hernandez, Olalde-Portugal, & Gonzalez-Castañeda, 2006; Gallegos-Infante, Rocha-Guzman, Gonzalez-Laredo, & Garcia-Casas, 2013), P. nigra (Felker et al, 2003), P. ruscifolia (Bernardi, Sanchez, Freyre, & Osella, 2010), and P. tamarugo (Astudillo et al, 2000); active compounds content and in vitro biological activity: P. alba (Cardozo et al, 2010;Cattaneo et al, 2016;Perez et al, 2014;Sciammaro et al, 2016), P. chilensis (Astudillo et al, 2000;Briones-Labarca, Muñoz, & Maureira, 2011;Schmeda-Hirschmann et al, 2015), P. laevigata (Gallegos-Infante et al, 2013), P. nigra (Cardozo et al, 2010;Perez et al, 2014), P. ruscifolia (Bernardi et al, 2010), and P. tamarugo (Astudillo et al, 2000); and in vivo biological activity: P. glandulosa (George, Lochner, & Huisamen, 2011;Huisamen, George, Dietrich, & Genade, 2013). Nutritionally, pods of Prosopis species are gluten free (Bernardi et al, 2010;Felker et al, 2013) and rich in good quality protein (Barba de la Rosa et al, 2006) or limited in sulfur amino acids (Felker & Bandurski, 1977;Fe...…”
Section: Introductionmentioning
confidence: 99%
“…The mesocarp of pods is rich in sugars (31%-50%), sucrose principally (Felker et al, 2013;Sciammaro et al, 2016). Trypsin inhibitors and phytohemagglutinins are present in seeds, which are denatured and inactivated upon heating (Barba de la Rosa et al, 2006;Gallegos-Infante et al, 2013). Pods of Prosopis species have been reported as a source of bioactive compounds (Felker et al, 2013;Schmeda-Hirschmann et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Authors have reported some variation in chemical composition of mesquite pods (de la Rosa et al, 2006) collected in a region with higher rainfall. Hence, some of the differences in the chemical composition may be due to climate or different soil conditions.…”
Section: Resultsmentioning
confidence: 99%
“…This has produced initiatives to consider underutilized plants, especially in areas in which basic crops are hard to establish due to salinity or lack of water (Barba de la Rosa et al, 2006). Among these, the Chilean algarrobo (Prosopis chilensis (Mol) Stuntz) has an interesting potential for the development of arid zones.…”
Section: Introductionmentioning
confidence: 99%